STRATEGI GURU TAHFIDZ DALAM MENGATASI KESULITAN MENGHAFAL AL-QUR’AN - Taufiq Ismail; S Suhadi; S Sulistyowati (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
This study aims to determine the strategies of tahfidz teachers in overcoming difficulties in memorizing the Qur'an. This research is a qualitative research with the subject of research at the Islamic boarding school Nidaul Quran Karangpandan Karanganyar. Collecting data using observation, interviews and documentation. Data analysis by means of data reduction, data display and data lever. The results of this study indicate that the characteristics of the students of the Nidaul Quran Islamic boarding school are the lack of religiosity from the family that can affect the ability of the memorization process. The teacher's step to overcome this problem is to use the talqin method and also the tikrar method, where students can then maintain and develop their memorization independently.